Voltammetric sizing and locating of spherical particles via cyclic voltammetry - Fietkau, N; Du, G; Matthews, S; Johns, M; Fisher, A; Compton, R (2007)
The size of a single spherical particle and its distance from the center of a microdisk electrode are determined by using a simple voltammetric procedure. A single spherical glass particle is positioned at an arbitrary distance from a microdisk electrode. Cyclic voltammograms for the oxidation of a model redox system are then recorded as a function of scan rate and compared to lattice Boltzmann simulations to deduce with good precision the radius of the spherical particle and the distance from the center of the electrode to the center of the particle. The radius of the sphere and its center-to-center distance are independently confirmed by microscopic images recorded at the time of the measurements. Excellent agreement between experiment and theory and independent direct observation are observed. © 2007 American Chemical Society.